Strategi Misi William Carey di India dan Implikasinya Bagi Pelayanan Misi Masa Kini - Tobi, Ongki Riando; Dju, Oktavia Adevin; Kote, Ivony Eunike Putri; Tanhidy, Jamin (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2021)
Expansion of evangelism to the whole world. William Carey is a modern evangelical figure. He was born into a poor family in Northamptonshire, England, on August 17, 1761 in a rural environment his parents were members of the Anglican Church and Carey received baptism in the church. Carey learned to make shoes from a shoemaker, Clarke Nichols. With the help of the English evangelist Carey was able to publish a translation of the New Testament into Bengali in 1801. The formulation of the problem in this discussion is the mission of William Carey and how it implies for believers today. The purpose of writing, with this writing can help readers to know about the life and evangelization of William Carey and how it implies for today's ministers of God. The church today has a huge responsibility. The church must have a great missionary spirit to carry out the Great Commission of Jesus Christ which He gave to the disciples when He was taken up to heaven (Matthew 28: 18-20) is the basis for everyone who has become a disciple of Christ.